Universal Equivalent Static Wind Loads of Fluctuating Wind Loads on Large-Span Roofs Based on POD Compensation. Issue 9 (September 2015) - Sun, Wuyi; Gu, Ming; Zhou, Xuanyi
Based on an existing equivalent static wind loads (ESWLs) method, this paper, with the help of POD compensation, presents a compensated ESWLs method of fluctuating wind loads on large-span roofs, which lowers the possible considerable errors produced in the existing method for those given target responses (TRs). In the two methods, TRs and POD modes of fluctuating wind loads on the structure based on the wind tunnel test are firstly computed. The uncompensated ESWLs and their approximate ESWLs-induced responses caused by the existing method are acquired. In the compensated ESWLs method, the response differences between TRs and ESWLs-induced responses in the existing method are used as the compensated values of TRs. According to the compensated values, the compensated POD mode and corresponding compensated contribution factor are constructed and respectively inserted to POD mode matrix and contribution factor vector in the existing method, which form a new POD mode matrix and a new contribution factor vector. The modified ESWLs distribution is then expressed by the product of above new matrix and new vector. The compensated ESWLs method is finally applied to an actual complex large-span roof. The computational results demonstrate that the compensated ESWLs method has the merits of clear physical meaning, simple computational principles and high computational accuracy, and it maybe meets the needs of the engineering designs if TRs are determined more reasonably.